Effect of Antimicrobials on Salmonella Spp. Strains Isolated from Poultry Processing Plants - L Mion (Brazilian Journal of Poultry Science)
ABSTRACT The routine use of antimicrobials in animal production for the treatment of infections, disease prevention, or as growth promoters is a predisposing factor for the development and dissemination of antimicrobial resistance. In food industries, sanitizers are used for the control of microbial colonization, and their efficacy depends on contact time and on the dilution of the products used. The present study assessed the effect of 12 antimicrobials and four commercial sanitizers on 18 Salmonella spp. strains isolated from poultry processing plants. None of the evaluated antimicrobials was 100% effective against the tested Salmonella spp. strains; however, 94% of the isolates were susceptible to ciprofloxacin, 77% to amoxicillin + clavulanic acid and to ampicillin, and 72% to enrofloxacin, whereas 100% of the isolates were resistant to penicillin G, 16% to tetracycline, and 11% to sulfonamide. The tested Salmonella spp. strains were 100% inhibited by peracetic acid after five minutes of contact, 0.5% by quaternary ammonium after 15 minutes, and 85.7% by chlorhexidine after 15 minutes. The results indicate the importance of testing of efficacy of antimicrobials used in animal production and in public health to monitor their action and the development of resistance.